ISSUES OF DEVELOPMENT OF METHODOLOGICAL CULTURE OF FUTURE TEACHERS IN THE PROCESS OF PROFESSIONAL TRAINING (Pedagogy of Higher and Secondary Education, 2022)
In article questions of improvement of vocational training of the future teachers through purposeful de velopment of methodological culture are brought up; the content and essence of methodological culure of the future teacher is considered; approaches purposeful to formation and developments in the conditions of profes sional formation are allocated.
Keywords: culure; methodological culture; vocational training